PELAKSANAAN TUGAS KELUARGA DI BIDANG KESEHATAN: MENGAMBIL KEPUTUSAN MENGENAI TINDAKAN KESEHATAN YANG TEPAT TERHADAP KEJADIAN HIPERTENSI PADA LANSIA DI KELURAHAN TIMBANGAN KECAMATAN INDRALAYA UTARA KABUPATEN OGAN ILIR - Madepan Mulia (Jurnal Kesehatan Panca Bhakti Lampung, 2018)
Hypertension is one of the number one causes of death globally that needs a good response. Results of Household Health Survey (SKRT) in 2007 showed that prevalence of hypertension disease in elderly in Indonesia is quite high, that is 83 per 1,000 household members. Data from the District Health Office Ogan Ilir in 2010 showed that hypertension is the third disease that attacks the elderly. This study aims to determine the relationship of family duties in the field of health: make decisions about appropriate health measures with the incidence of hypertension in the elderly. This research is a quantitative analytical research with cross sectional approach. This study was conducted on families with elderly family members aged over 60 years scattered in the village of Timbangan, which amounted to 94 respondents, using a questionnaire tool. To test the relationship used analysis using Chi-Square test. The results showed that there was a relationship between the implementation of family duty in the field of health: make decisions about appropriate health measures with the incidence of hypertension (p = 0.000). From the results of this study suggested to the family in order to improve the degree of health and to overcome the health problems of family members, especially the elderly, by performing family duties in the field of health is make decisions about appropriate health measures for the elderly.